Optimized lead-acid grid architectures for automotive lead-acid batteries: An electrochemical analysis. (10th March 2021) - Calborean, Adrian; Murariu, Teodora; Morari, Cristian
Highlights: Hierarchical approach projection that employs rectangular shapes for the novel grids design. Predictions of current distribution by a numerical algorithm across the electrodes grid surface. SoH prediction by electrochemical impedance spectroscopy technique. An improved lifetime performance was obtained, compared to industrial electrodes. We reduced the lead quantity in the manufacturing process by changing their configuration. Abstract: A variety of technological approaches of lead-acid batteries have been employed during the last decades, within distinguished fabrication features of electrode grid composition, electrolyte additives, or oxide paste additives embodiment. We proposed in this study, a particular path for improving the efficiency of positive grids by developing two novel geometry designs of lead-acid battery metallic grids. Our projection is based on a hierarchical approach that employed exclusively rectangular shapes for the structural configuration of grids. The intensity of current distribution was firstly evaluated by a numerical algorithm across the electrodes grid surface, thus allowing measuring the propagation of the electric charge emitted from each point inside of the grid. The novel fabricated prototypes were investigated by electrochemical impedance spectroscopy, following a controlled aging procedure. Two distinct parameters were investigated for evaluation of batteries lifetime: i) a time-dependent analysis of Constant Phase Element – Q parameter at 75% SoC partially discharged, and ii) the resonance frequency of the circuit. To confirm our improvements, we compared the data with the ones of an industrial grid model. An increment of battery lifetime was obtained for one prototype, with an estimation growth of 25% - 28% over the usual industrial electrode, while for the later a slightly improved lifetime efficiency of about 10% was resulted. Graphical abstract: Fig.1. Left: Typical distribution of electric potential in the grid during discharge (Indicated: 20 equipotential contour lines, respectively the three areas used as a guide for grid design, defined according to the density of equipotential field lines. Right: representation of the gradients in the plate at discharge; the regions with "homogenous" gradients are also represented. Colors are used to indicate the qualitative distributions of absolute value for gradients from small values (bottom of the plate) to large ones at the top. Image, graphical abstract